Determinant Organization Commitment and Development Organization: Analysis Servant Leadership, Transformational Leadership, Transactional Leadership - Primadi Candra Susanto; Lira Agusinta; Aswanti Setyawati; Anggia Rettrisunz Pim Panjaitan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find out what factors can influence the Development Organization at Company, This article aims to review and synthesize a literature review related to and Servant Leadership, Transformational Leadership, Transactional Leadership, Organization Commitment see the research results of the variables to be reviewed and whether there is an influence between one variable and another. This study uses a literature review by looking for references related to the variables of several international articles. This study provides an overview of the articles obtained by describing the influence between variables. The purpose of the study was to look at a mini-review of 20 selected articles related to variables and present findings, using a qualitative method with a literature review of the results collected. The results of this study there are several articles that have an influence and still have to be continued in further research with the same variables perhaps with different objects.